Model Untuk Meningkatkan Kualitas Perkuliahan Analisis Real - Alfito Fatihah; Rusi Ulfa Hasanah; Atika Rahmah; Mayang Nabila (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Real analysis is a course that requires formal proof of a formal definition. Almost all students have difficulty learning real analysis. These problems require the provision of learning models that can serve students who learn real analysis. The purpose of this study is to provide an overview or description of the Model to improve the quality of real analysis lectures. The method used in this study is Systematic Literature Review. The results of the study concluded that models to improve the quality of real analysis lectures are very diverse. Learning models such as the use of Flow Proof and Extended Triad Level ++ Learning Models, to the application of learning modules such as Project-Based Learning Modules can be effectively and efficiently used to improve the quality of real analysis lectures.